Microwave pretreatment of sprouted mung beans before hot-air and infrared drying process - Fakhreddin Salehi (فناوری‌های جدید در صنعت غذا)
Sprouting enhances the nutritional and quality characteristics of mung beans (Vigna radiata L.). In this study impacts of infrared radiation and hot-air drying on microwave-pretreated mung bean sprouts were examined. The microwave process was performed for 0, 15, 30, 45, and 60 s before hot-air and infrared dehydration of sprouted mung beans. Microwave pretreatment decreased drying time of sprouted mung beans. Increasing the microwave pretreatment time from 0 to 60 s caused drying time of samples inside the hot-air dryer to decrease from 205 min to 130 min (p<0.05). Drying time of sprouts in the infrared dryer was significantly less than the hot-air dryer (p<0.05). Effective moisture diffusivity coefficient (Deff) calculated by Fick's second law, varied in the range of 1.06×10-10 - 1.60×10-10 m2s-1, and 0.98×10-9 - 1.15×10-9 m2s-1, for hot-air and infrared dried samples, respectively. Experimental data for drying curves were fitted to various thin-layer equations, and the Midilli equation was best suited to explain drying kinetics of sprouted mung beans. Average rehydration ratio of dried sprouted mung beans in hot-air and infrared dryers were 262.55%, and 211.65%, respectively. In summary, the microwave pretreatment (about 60 sec) and use of infrared dryer is appropriate drying technique for sprouted mung beans with faster mass transfer and shorter drying time.